Paste for electronic components

JP7652288B2Active Publication Date: 2025-03-27MURATA MFG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023564784
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-01
Filing Date
2022-10-15
Publication Date
2025-03-27
Estimated Expiration
2042-10-15

Smart Images

  • Figure 0007652288000016
    Figure 0007652288000016
  • Figure 0007652288000017
    Figure 0007652288000017
  • Figure 0007652288000001
    Figure 0007652288000001
Patent Text Reader

Abstract

The present invention provides a paste for electronic components, the paste containing a binder that has the characteristics of a cellulose resin and the characteristics of a terminal functional group derived from a resin of another kind or a low-molecular weight material of another kind at the same time with good compatibility, and the paste enabling the achievement of a smooth coating film. The present invention relates to a paste for electronic components, the paste containing inorganic particles, a dispersant, a binder and an organic solvent. With respect to this paste for electronic components, the binder contains, for example, at least a copolymer which is represented by general formula 1, wherein a first binding site at one end of the molecular chain of a cellulose resin is bonded to a resin of another kind or a low-molecular weight material of another kind by an ester bond or an amide bond.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a paste for electronic components, which is used in the production of electronic components and contains inorganic particles, a dispersant, a binder, and an organic solvent, and in particular to an improvement in the binder. [Background technology]

[0002] For example, with the trend toward higher capacitance and smaller size of multilayer ceramic capacitors, there is a demand for more multi-layered and thinner dielectric sheets and internal electrode layers. In addition, there are demands for good adhesion between the dielectric layers and the internal electrode layers, good printability of the internal electrode layers, and high strength of the internal electrode layers.

[0003] Conventionally, conductive pastes used to form internal electrode layers have used cellulose-based resins as binders, but cellulose-based resins have the problem that they can cause delamination due to insufficient adhesion with acetal-based resins, which are commonly used as binders in dielectric sheets.

[0004] Therefore, for example, as described in Japanese Patent No. 5299904 (Patent Document 1), a technology has been proposed in which a cellulose-based resin and an acetal-based resin are blended as a binder used in a conductive paste to improve the adhesion between the dielectric layer and the internal electrode layer, and, for example, as described in Japanese Patent No. 5224722 (Patent Document 2), a technology has been proposed in which a cellulose-based resin and an acetal-based resin are blended to maintain the effect of improving the adhesion between the dielectric layer and the internal electrode layer, while further improving the compatibility between the cellulose-based resin and the acetal-based resin and improving storage stability.

[0005] However, the compatibility of the resin blends described in Patent Documents 1 and 2 is relatively low. Therefore, for example, the technology described in International Publication No. 2015 / 107811 (Patent Document 3) aims to improve adhesion and compatibility by using a binder crosslinked with a dicarboxylic acid-containing binder using hydroxyl groups possessed by a cellulose-based resin and an acetal-based resin. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 5299904 [Patent Document 2] Patent No. 5224722 [Patent Document 3] International Publication No. 2015 / 107811 Summary of the Invention [Problem to be solved by the invention]

[0007] In general, the viscosity of a polysaccharide solution containing many hydroxyl groups increases with the concentration of the polysaccharide, and the solution turns into a gel. When the concentration of polysaccharides in a liquid increases, the polysaccharide molecules become entangled and partially bonded, forming a mesh-like network with these parts as base points, and the entire solution becomes a gel.

[0008] In Patent Document 3, the cellulose-based resin and the acetal-based resin are bonded together by using a binder having a lower molecular weight than the acetal-based resin to make the less reactive hydroxyl groups remaining in the cellulose-based resin more likely to react with the acetal-based resin.

[0009] However, this also makes it easier for crosslinked products between cellulose resins and between acetal resins to form. In this case, crosslinked products with a network structure may be formed, and sometimes crosslinked products with a large ring structure may be formed. In particular, crosslinked products consisting only of cellulose resins may lead to gelation as in the above example, and if they are present locally in the paste for electronic components, the smoothness of the coating film such as the internal electrode layer may be impaired.

[0010] The adhesion phenomenon of polymers is largely influenced by the molecular structure of the polymer main chain and side chain, but it is speculated that the molecular structure of the polymer end is the next most influential factor. This is because polymers have very large molecular sizes and are entangled with each other, making it difficult for the entire polymer to move during the adhesion process, and it is thought that the molecular structure of the polymer end, which has a relatively high degree of freedom of movement, contributes to adhesion, especially in the initial adhesion process where time and temperature are limited. Therefore, in addition to the method of bonding a different type of resin to a cellulose-based resin to improve the adhesion to a dielectric sheet, it is also thought that a method of introducing terminal functional groups that can form low-molecular hydrogen bonds, coordinate bonds, dipole interactions, acid-base interactions, etc., that contribute to improving the adhesion strength, at the end of the cellulose-based resin is also effective.

[0011] Therefore, an object of the present invention is to provide a paste for electronic components, in which the binder has both the properties of a cellulose-based resin and the properties of a terminal functional group derived from another type of resin or another type of low-molecular-weight resin, and the compatibility between the two is good, and a smooth coating film can be obtained. [Means for solving the problem]

[0012] The present invention is directed to a paste for electronic components, comprising inorganic particles, a dispersant, a binder, and an organic solvent, the binder comprising: (A) A copolymer represented by the following general formula 1 or the following general formula 2 in which a first bond at one end of a molecular chain of a cellulose-based resin is linked to another type of resin or another type of low molecular weight molecule via an ester bond or an amide bond; or (B) A copolymer represented by the following general formula 3 or 4, in which a first bond at one end of a molecular chain of a cellulose-based resin is an ester bond or an amide bond, and a second bond (X) is connected to a different resin via a binder (R3); It is characterized by including at least

[0013] [ka]

[0014] [ka]

[0015] In the formula, R1 represents hydrogen, an alkyl group, a hydroxyalkyl group, or an acyl group, and R2 represents another type of resin or an alkyl group.

[0016] [ka]

[0017] [ka]

[0018] In the formula, R1 represents hydrogen, an alkyl group, a hydroxyalkyl group, or an acyl group, R4 represents another type of resin, R3 represents an alkyl- or sulfide-containing linking agent, and X represents an ester or amide bond. Effect of the Invention

[0019] According to the paste for electronic parts of the present invention, the binder contained therein has both the characteristics of the cellulose resin and the characteristics of the terminal functional group derived from another type of resin or another type of low molecule, and can realize good compatibility between the cellulose resin and the other type of resin or another type of low molecule. Also, since the binder is less likely to produce a resin that leads to gelation, it is possible to obtain a paste for electronic parts that does not impair the smoothness of the coating film. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 shows a 1H-NMR spectrum of an ethyl cellulose derivative. [Diagram 2] FIG. 1 shows the correlation between the molecular weight of ethyl cellulose determined by NMR and that determined by GPC. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The paste for electronic components according to the present invention contains inorganic particles, a dispersant, a binder, and an organic solvent. (A) A copolymer represented by the following general formula 5 or the following general formula 6, in which a first bond at one end of a molecular chain of a cellulose-based resin is linked to another type of resin or another type of low molecular weight molecule via an ester bond or an amide bond; or (B) A copolymer represented by the following general formula 7 or 8, in which a first bond at one end of a molecular chain of a cellulose-based resin is an ester bond or an amide bond, and a second bond (X) is connected to a different resin via a binder (R3); At least

[0022] [ka]

[0023] [ka]

[0024] In the formula, R1 represents hydrogen, an alkyl group, a hydroxyalkyl group, or an acyl group, and R2 represents another type of resin or an alkyl group. The alkyl group serving as R2 preferably has 1 to 4 carbon atoms.

[0025] [ka]

[0026] [ka]

[0027] In the formula, R1 represents hydrogen, an alkyl group, a hydroxyalkyl group, or an acyl group, R4 represents another type of resin, R3 represents an alkyl- or sulfide-containing linking agent, and X represents an ester or amide bond.

[0028] The method for bonding the cellulose-based resin contained in the binder with the other type of resin or the other type of low molecule may be the commonly used ester bond or amide bond reaction, so long as the other type of resin or the other type of low molecule has a hydroxyl group or an amino group, the range of materials to be selected is wide.

[0029] Therefore, if it is desired to impart the properties of a terminal functional group derived from a different type of resin or a different type of low molecule in addition to the properties of viscosity expression, elasticity, printability, etc., possessed by a cellulose-based resin, (e.g., viscosity properties, adhesion to a sheet binder containing a different type of resin, etc.), by combining a cellulose-based resin with a different type of resin or a different type of low molecule using the above-mentioned synthesis method, it is possible to obtain a binder in which the properties of the terminal functional group derived from the different type of resin or a different type of low molecule are added to the properties of the cellulose-based resin.

[0030] In addition, when a different type of resin is bonded in this invention, the compatibility between the cellulose resin and the different type of resin can be improved. Furthermore, since the cellulose resin is bonded to the different type of resin by using one of the terminal carboxyl groups, only a graft structure can be formed, not a network structure of the bond between the cellulose resins, and as a result, the resin that leads to gelation is unlikely to be formed, and the smoothness of the coating film formed by the paste for electronic components according to this invention is unlikely to be impaired.

[0031] In this invention, when an ester group or an amide group is introduced as a terminal functional group derived from another type of low molecule, the adhesion can be improved by hydrogen bonding between the cellulose resin and the acetal resin that is usually used as a binder in dielectric sheets. In addition, since it does not show any peculiar behavior such as adsorption to powder, the smoothness of the paste coating is also excellent.

[0032] In the above embodiment (B), the binder (R3) is a binder containing alkyl or sulfide, but does not generate bonds between different resins except when a vinyl or allyl group is introduced and a bonding reaction is carried out by radicals. Therefore, it is preferable not to use a binder containing a vinyl or allyl group.

[0033] In the case of bonding a different type of resin in this invention, by selecting the suitable conditions shown in the experimental examples described later, even in the blending ratio of the cellulose-based resin and the different type of resin that is likely to cause gelation between the cellulose-based resins themselves, or in the reaction conditions using the binder (R3) described in (B) above, only a graft structure is formed and it is difficult to form a resin that leads to gelation, and therefore it is possible to prevent the smoothness of the coating film from being impaired.

[0034] The cellulose-based resin is preferably a cellulose ether having a carboxyl group at one end of the molecular chain, because it is more practical to obtain a cellulose ether having a carboxyl group at one end of the molecular chain as the cellulose-based resin, taking into consideration the synthesis reaction scheme described later.

[0035] The cellulose ether is preferably an alkyl cellulose.

[0036] The terminal functional groups derived from other types of resins and other types of low molecular weight compounds are intended, for example, to supplement properties that are not present in the cellulose-based resin or to enhance the properties of the cellulose-based resin.

[0037] The different resin is not particularly limited, and may be, for example, at least one resin selected from the group consisting of polyvinyl acetal resins, acrylic resins, polycarbonate resins, polyurethane resins, polyether resins, and polyester resins having a hydroxyl group or an amino group.

[0038] As the terminal functional group derived from another type of low molecular weight, an ester group or an amide group, which is relatively favorable for hydrogen bonding and can improve adhesive strength, is applied.

[0039] The content ratio of the cellulose-based resin to the other resin is preferably in the range of 80:20 to 20:80 in terms of mass, and more preferably in the range of 60:40 to 40:60 in terms of mass. By selecting such a ratio, it is possible to ensure that the performance of both the cellulose-based resin and the other resin can be exhibited.

[0040] The dispersant is not particularly limited and may be a typical low molecular weight one-end adsorption dispersant or a comb-shaped polymer dispersant, but is particularly preferably a polycarboxylic acid dispersant.

[0041] The inorganic particles contained in the paste for electronic components according to the present invention preferably include at least one of ceramic particles and metal particles. For example, a paste for forming a dielectric layer in a multilayer ceramic capacitor includes at least ceramic particles, and a paste for forming an internal electrode layer includes at least metal particles. The ceramic particles include at least one element selected from Ba, Ti, Ca, Zr, and Sr, for example. The metal particles include at least one metal selected from Cu, Ni, Au, and Ag, for example.

[0042] <Experimental Example> In this experimental example, the electronic component paste was a conductive paste for obtaining an internal electrode layer of a multilayer ceramic capacitor, and 26 types of conductive paste samples containing various binders were prepared.

[0043] Details of the 26 types of samples prepared in this experimental example are shown in Table 3 below. Among these samples, the "Example" contains a binder in which a cellulose-based resin is bonded to another type of resin, and the "Comparative Example" contains a binder which is simply a blend of a cellulose-based resin and another type of resin.

[0044] A cellulose derivative having a carboxyl group at one end was synthesized as follows. Here, a synthesis method using ethyl cellulose, which is a type of cellulose derivative and is widely used in pastes for electronic components, was used as the synthesis method for the cellulose derivative having a carboxyl group at one end. The synthesis method is not limited to the method shown below.

[0045] (1) Oxidation of the reducing end of cellulose to produce cellulose with one carboxylated end A 50% aqueous solution of sodium hydroxide (1680g) was added to a water-dispersed slurry of cellulose (solid content 1440g). After that, sodium anthraquinone-2-sulfonate (24g) dissolved in 30% hydrogen peroxide was added and stirred to oxidize the reducing end of the cellulose, and then filtration and washing with water were performed to obtain cellulose with one end carboxylated. This reaction is a reaction in which the formyl group, which is in a ring-opened state and has a formyl group among the tautomers of the reducing end of cellulose, is oxidized to a carboxyl group.

[0046] Various methods are known for the oxidation reaction of the reducing end of cellulose or the formyl group of ring-opened sugar.

[0047] (2) Deprotonation reaction with sodium hydroxide A 50% aqueous solution of sodium hydroxide was added to an aqueous solution of cellulose with one end carboxylated, and the mixture was stirred at 60°C for 20 minutes to obtain alkali cellulose in which the hydroxyl group was -ONa and one end was -COONa.

[0048] (3) Ethoxylation (etherification) reaction and ethyl esterification reaction with ethyl chloride Alkaline cellulose and ethyl chloride were stirred in a 0.5 MPa pressure cooker at 110°C for 12 hours to obtain ethyl cellulose with -OEt as the hydroxyl group and -COONa, -COOH, or -COOEt as one end. The amount of sodium hydroxide and the amount of ethyl chloride added were adjusted so that the degree of ethoxylation (DS) for the three OH groups of the monomer unit of the cellulose obtained at this time was in the range of 2.46 to 2.58 (ethoxylation degree 48.0 to 49.5 mass%).

[0049] In this synthesis, the etherification reaction proceeds more rapidly than the esterification reaction, so little is esterified to -COOEt.

[0050] (4) Hydrolysis of esters The reaction of ethyl cellulose with one end being -COOEt was carried out by hydrolysis to convert the -COOEt to -COOH, obtaining ethyl cellulose with a hydroxyl group of -OEt (degree of substitution 2.5) and one end being -COONa (carboxylate) or -COOH (carboxyl group).

[0051] There are various conditions for hydrolysis, but the reaction can also proceed by adding water to an alcohol solvent and heating. To make the reaction more efficient, it is also a good idea to add a catalyst. Note that since esterification does not proceed easily during the etherification reaction using ethyl chloride, it is possible to obtain ethyl cellulose with most of the ethyl cellulose at one end being -COONa (carboxylate) or -COOH (carboxyl group) even without carrying out this step.

[0052] (5) Washing and drying After removing salts and by-products by washing with hot water, the solid was dried under reduced pressure to obtain a solid one-terminal carboxylated ethyl cellulose with an ethoxylation degree of 2.5, in which one terminal was -COONa (carboxylate) or -COOH (carboxyl group) and the other terminal was -OEt (ether). By adjusting the number average molecular weight of the cellulose used initially within the range of 10,000 to 100,000, four types of one-terminal carboxylated ethyl cellulose were produced: the first one-terminal carboxylated ethyl cellulose with a number average molecular weight Mn of 13,000 (shown as "CC1" in Table 3), the second one-terminal carboxylated ethyl cellulose with a number average molecular weight Mn of 20,000, the third one-terminal carboxylated ethyl cellulose with a number average molecular weight Mn of 54,000, and the fourth one-terminal carboxylated ethyl cellulose with a number average molecular weight Mn of 88,000 (shown as "CC4" in Table 3).

[0053] The number average molecular weight was determined by gel permeation chromatography (GPC) measurement using polystyrene as a standard polymer and tetrahydrofuran (THF) as an eluent.

[0054] (6) Determination of carboxyl groups in one-terminal carboxylated ethyl cellulose The amount of carboxyl groups in the one-terminated ethyl cellulose synthesized as above was 1 Quantification was performed using H-NMR measurement. Since it was expected that normal NMR measurement would lack the sensitivity to quantify the small amount of terminal carboxyl groups, a trimethylsilyl (TMS) derivatization method was used.

[0055] The TMS derivatization method is a method of replacing the hydrogen of the hydroxyl group contained in the carboxyl group of ethyl cellulose with a trimethylsilyl group (Si(CH3)3). This derivatization changes the number of hydrogen atoms in the carboxyl group from 1H to 9H, so 1 The detection sensitivity of H-NMR is increased by 9 times.

[0056] The derivatized product is obtained by adding ethyl cellulose and the derivatization reagent (BSTFA) to dehydrated chloroform solvent and heating at 70°C for 1 hour. Since the derivatization reagent acts on both the hydroxyl and carboxyl groups of ethyl cellulose, the amount of the reagent added is approximately 1.5 times the molar amount of the hydroxyl and terminal carboxyl groups of ethyl cellulose. It was confirmed that the quantitative values ​​of the TMS-converted hydroxyl and carboxyl groups do not change even when the amount of the reagent added exceeds 1.5 times the molar amount. The solution after the reaction is returned to room temperature and vacuum dried, and then GPC fractionation is performed to remove the solvent and unreacted derivatization reagent, obtaining a dried product of the derivatized product. This dried product is redissolved in deuterated chloroform, the solvent for NMR measurement, and 1 H-NMR measurement was carried out. 1 The H-NMR spectrum is shown in Figure 1.

[0057] Ethyl cellulose derivatives 1 In the H-NMR spectrum, a peak due to derivatization of the carboxyl group is detected at 0.3 ppm, as indicated by the arrow in Figure 1. 1The concentration of carboxyl groups in ethyl cellulose was determined by calculating the molar ratio of each from the peak area ratio of the cellulose skeleton, ethoxy group, carboxyl group, and hydroxyl group observed by H-NMR. Table 1 shows the quantitative results of the carboxyl groups and the average molecular weight of the corresponding samples. Note that GPC was measured in THF solvent, and the number average molecular weight was calculated in terms of polystyrene.

[0058] [Table 1]

[0059] The number of carboxyl groups in ethyl cellulose decreases with increasing molecular weight, suggesting that the carboxyl groups are present at sites that depend on the molecular weight. Since the terminal concentration of polymer decreases with increasing molecular weight of a single molecular chain, it is considered that the quantified carboxyl groups are present at the terminals. In addition, from the perspective of the synthesis reaction scheme of the sample, it can be determined that the carboxyl group analyzed by NMR is present at one terminal.

[0060] Furthermore, assuming that the carboxyl group determined by NMR exists at one end of the ethyl cellulose, the molecular weight of the ethyl cellulose was calculated by determining the number of repeating units of the ethyl cellulose. Table 2 shows the average molecular weights determined by NMR and GPC.

[0061] [Table 2]

[0062] Since the average molecular weight determined by GPC is calculated in terms of polystyrene, the absolute value of the average molecular weight determined by NMR does not match that of the average molecular weight determined by GPC. However, as shown in Figure 2, when comparing the molecular weight values ​​determined by both methods for samples with different molecular weights, a high correlation was observed. This result indicates that a carboxyl group exists at one end of the ethyl cellulose, and it can be said that NMR quantified the carboxyl group present at one end.

[0063] Next, copolymers according to Examples 1 to 14 shown in Table 3 were synthesized in which the cellulose derivatives having a carboxyl group at one end obtained as described above (the first to fourth one-end carboxylated ethyl celluloses) were linked to different resins.

[0064] [Example 1] (First synthesis of copolymer of one-terminal carboxylated ethyl cellulose and polyvinyl acetal resin) Five parts by mass of the first one-terminal carboxylated ethyl cellulose as a cellulose derivative having a one-terminal carboxyl group, and five parts by mass of a polyvinyl acetal resin having a hydroxyl group as another resin ("BL-S" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn = 27000) were dried under reduced pressure, and 90 parts by mass of ethyl acetate were added and dissolved at 50 ° C. under a nitrogen atmosphere. Diisopropylcarbodiimide was added as a condensation agent in an amount of 1.1 times the number of moles of the first one-terminal carboxylated ethyl cellulose, and dimethylaminopyridine was added as a reaction accelerator in an amount of 0.01 times the number of moles of the condensation agent, and the mixture was stirred at a temperature of 50 ° C. for 24 hours to react, thereby preparing a binder solution. Thereafter, the ethyl acetate was distilled off to obtain a solid, and a copolymer was obtained by ester bonding between the cellulose derivative having a one-terminal carboxyl group and the polyvinyl acetal resin.

[0065] The copolymer obtained was analyzed by FT-IR (Fourier transform infrared spectroscopy), 1 Analysis by H-NMR confirmed the formation of ester bonds, and analysis by GPC confirmed that the number average molecular weight was larger than that of the raw material resin, confirming the progress of the reaction.

[0066] Thereafter, in order to prepare a conductive paste, 10 parts by mass of the obtained copolymer was dissolved in 90 parts by mass of dihydroterpinyl acetate to prepare a binder solution.

[0067] [Example 2] (Synthesis of the fourth copolymer of one-terminal carboxylated ethyl cellulose and polyvinyl acetal resin) The cellulose derivative having a carboxyl group at one end was changed to the fourth one-end carboxylated ethyl cellulose, and the other resin was changed to a polyvinyl acetal resin having a hydroxyl group ("BH-S" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn = 63,000), but the reaction was carried out under the same conditions as in Example 1 to prepare a binder solution containing a copolymer formed by an ester bond between a cellulose derivative having a carboxyl group at one end and a polyvinyl acetal resin.

[0068] [Example 3] (First synthesis of copolymer of one-terminal carboxylated ethyl cellulose and polyvinyl acetal resin) Except for changing the different resin to a polyvinyl acetal resin having a hydroxyl group ("BH-S" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn = 63000), the reaction was carried out under the same conditions as in Example 1 to prepare a binder solution containing a copolymer formed by an ester bond between a cellulose derivative having a carboxyl group at one end and a polyvinyl acetal resin.

[0069] [Example 4] (Synthesis of the fourth copolymer of one-terminal carboxylated ethyl cellulose and polyvinyl acetal resin) Except for changing the cellulose derivative having a carboxyl group at one end to the fourth ethyl cellulose having a carboxylated end at one end, the reaction was carried out under the same conditions as in Example 1 to prepare a binder solution containing a copolymer formed by an ester bond between the cellulose derivative having a carboxyl group at one end and a polyvinyl acetal resin.

[0070] [Example 5] (Synthesis of first copolymer of one-terminal carboxylated ethyl cellulose and acrylic resin) Except for changing the different resin to an acrylic resin having a hydroxyl group (the main monomer was isobutyl methacrylate, and the acrylic resin contained 5 mol% of 2-hydroxyethyl methacrylate, the number average molecular weight Mn=21000), the reaction was carried out under the same conditions as in Example 1 to produce a binder solution containing a copolymer formed by an ester bond between a cellulose derivative having a carboxyl group at one end and an acrylic resin.

[0071] [Example 6] (First synthesis of copolymer of one-terminal carboxylated ethyl cellulose and aliphatic polycarbonate resin) Except for changing the different resin to an aliphatic polycarbonate resin having a hydroxyl group (polypropylene carbonate, number average molecular weight Mn = 24000), the reaction was carried out under the same conditions as in Example 1 to produce a binder solution containing a copolymer formed by an ester bond between a cellulose derivative having a carboxyl group at one end and a polycarbonate resin.

[0072] [Example 7] (Synthesis of the first copolymer of one-terminal carboxylated ethyl cellulose and polyurethane resin) A binder solution containing a copolymer formed by an ester bond between a cellulose derivative having a carboxyl group at one end and a polyurethane resin was produced by reacting under the same conditions as in Example 1, except that the different resin was changed to a polyurethane resin having a hydroxyl group (a prepolymer consisting of polyester polyol PMPA (poly(3-methyl-1,5-pentanediol adipate)diol), polyether polyol PPG (poly(propylene glycol)diol), and diisocyanate IPDI (isophorone diisocyanate), to which IPDI (isophorone diamine) and DETA (diethylenetriamine) were added as chain extenders and ethanolamine as a terminator, respectively, with a number average molecular weight Mn of 24,000).

[0073] [Example 8] (Synthesis of the first copolymer of one-terminal carboxylated ethyl cellulose and polyurethane resin) A binder solution containing a copolymer formed by an amide bond between a cellulose derivative having a carboxyl group at one end and a polyurethane resin was produced by reacting the cellulose derivative and the polyurethane resin under the same conditions as in Example 1, except that the resin was changed to a polyurethane resin having an amino group (a prepolymer consisting of polyester polyol PMPA (poly(3-methyl-1,5-pentanediol adipate)diol), polyether polyol PPG (poly(propylene glycol)diol), and diisocyanate IPDI (isophorone diisocyanate), to which IPDI (isophorone diamine) and DETA (diethylenetriamine) were added as chain extenders and ethylenediamine as a terminator, with a number average molecular weight Mn of 26,000).

[0074] [Example 9] (Synthesis of the first copolymer of one-terminal carboxylated ethyl cellulose and polyether resin) Except for changing the different resin to a polyether resin having a hydroxyl group (mPEG, number average molecular weight Mn = 10,000), the reaction was carried out under the same conditions as in Example 1 to prepare a binder solution containing a copolymer formed by an ester bond between a cellulose derivative having a carboxyl group at one end and a polyether resin.

[0075] [Example 10] (Fourth synthesis of copolymer of one-terminal carboxylated ethyl cellulose and aliphatic polyester resin) Except for changing the different resin to an aliphatic polyester resin having a hydroxyl group (polycaprolactone, number average molecular weight Mn = 45,000), the reaction was carried out under the same conditions as in Example 2 to produce a binder solution containing a copolymer formed by an ester bond between a cellulose derivative having a carboxyl group at one end and a polyester resin.

[0076] In the following Examples 11 to 14, the content ratio of the cellulose derivative having a carboxyl group at one end and the different resin was changed to several ratios other than 50:50.

[0077] [Example 11] (First synthesis of copolymer of one-terminal carboxylated ethyl cellulose and polyvinyl acetal resin) The reaction was carried out under the same conditions as in Example 1, except that the first one-terminal carboxylated ethyl cellulose as the cellulose derivative having a one-terminal carboxyl group was changed to 6 parts by mass, and the other resin was changed to 4 parts by mass of a polyvinyl acetal resin having a hydroxyl group ("BL-S" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn = 27,000), to produce a binder solution containing a copolymer formed by an ester bond between the cellulose derivative having a one-terminal carboxyl group and the polyvinyl acetal resin.

[0078] [Example 12] (First synthesis of copolymer of one-terminal carboxylated ethyl cellulose and polyvinyl acetal resin) A binder solution containing a copolymer formed by an ester bond between a cellulose derivative having a carboxyl group at one end and a polyvinyl acetal resin having an ester bond was prepared by reacting under the same conditions as in Example 1, except that the first one-terminal carboxylated ethyl cellulose as the cellulose derivative having a carboxyl group at one end was changed to 8 parts by mass, and the other resin was changed to 2 parts by mass of a polyvinyl acetal resin having a hydroxyl group ("BL-S" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn = 27,000).

[0079] [Example 13] (First synthesis of copolymer of one-terminal carboxylated ethyl cellulose and polyvinyl acetal resin) A binder solution containing a copolymer formed by an ester bond between a cellulose derivative having a carboxyl group at one end and a polyvinyl acetal resin having a hydroxyl group ("BL-S" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn = 27000) was prepared by reacting under the same conditions as in Example 1, except that the first one-terminal carboxylated ethyl cellulose as the cellulose derivative having a carboxyl group at one end was changed to 4 parts by mass and the other resin was changed to 6 parts by mass.

[0080] [Example 14] (First synthesis of copolymer of one-terminal carboxylated ethyl cellulose and polyvinyl acetal resin) The reaction was carried out under the same conditions as in Example 1, except that the amount of the first one-terminal carboxylated ethyl cellulose as the cellulose derivative having a one-terminal carboxyl group was changed to 2 parts by mass, and the amount of the other resin was changed to 8 parts by mass of a polyvinyl acetal resin having a hydroxyl group ("BL-S" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn = 27,000), to produce a binder solution containing a copolymer formed by an ester bond between the cellulose derivative having a one-terminal carboxyl group and the polyvinyl acetal resin.

[0081] Next, binder solutions in which a cellulose derivative having a carboxyl group at one end and another type of resin were simply mixed were obtained as Comparative Examples 1 to 10. It should be noted that Comparative Examples 1 to 10 share the same different type of resin as Examples 1 to 10, respectively.

[0082] [Comparative Example 1] (Preparation of a first mixture of one-terminal carboxylated ethyl cellulose and polyvinyl acetal resin) A binder solution was prepared by dissolving 5 parts by mass of a first one-terminal carboxylated ethyl cellulose as a cellulose derivative having a one-terminal carboxyl group, and 5 parts by mass of a polyvinyl acetal resin having a hydroxyl group ("BL-S" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn = 27,000) as another type of resin in 90 parts by mass of dihydroterpinyl acetate.

[0083] [Comparative Example 2] (Preparation of the fourth mixture of one-terminal carboxylated ethyl cellulose and polyvinyl acetal resin) A binder solution was prepared under the same conditions as in Comparative Example 1, except that the cellulose derivative having a carboxyl group at one end was changed to the fourth one-end carboxylated ethyl cellulose, and the other resin was changed to a polyvinyl acetal resin having a hydroxyl group ("BH-S" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn = 63,000).

[0084] [Comparative Example 3] (Preparation of a first mixture of one-terminal carboxylated ethyl cellulose and polyvinyl acetal resin) A binder solution was prepared under the same conditions as in Comparative Example 1, except that the different resin was changed to a polyvinyl acetal resin having a hydroxyl group ("BH-S" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn = 63000).

[0085] [Comparative Example 4] (Preparation of the fourth mixture of one-terminal carboxylated ethyl cellulose and polyvinyl acetal resin) A binder solution was prepared under the same conditions as in Comparative Example 1, except that the cellulose derivative having a carboxyl group at one end was changed to the fourth one-end carboxylated ethyl cellulose.

[0086] [Comparative Example 5] (Preparation of first mixture of one-terminal carboxylated ethyl cellulose and acrylic resin) A binder solution was prepared under the same conditions as in Comparative Example 1, except that the different resin was changed to an acrylic resin having a hydroxyl group (the main monomer was isobutyl methacrylate, the acrylic resin contained 5 mol% of 2-hydroxyethyl methacrylate, and the number average molecular weight Mn was 21,000).

[0087] [Comparative Example 6] (Preparation of the first mixture of one-terminal carboxylated ethyl cellulose and an aliphatic polycarbonate resin) A binder solution was prepared under the same conditions as in Comparative Example 1, except that the different resin was changed to an aliphatic polycarbonate resin having a hydroxyl group (polypropylene carbonate, number average molecular weight Mn=24000).

[0088] [Comparative Example 7] (Preparation of first mixture of one-terminal carboxylated ethyl cellulose and polyurethane resin) A binder solution was prepared under the same conditions as in Comparative Example 1, except that the different resin was changed to a polyurethane resin having a hydroxyl group (a prepolymer consisting of polyester polyol PMPA (poly(3-methyl-1,5-pentanediol adipate)diol), polyether polyol PPG (poly(propylene glycol)diol), and diisocyanate IPDI (isophorone diisocyanate), to which IPDI (isophorone diamine) and DETA (diethylenetriamine) were added as chain extenders and ethanolamine as a terminator, and the number average molecular weight Mn was 24,000).

[0089] [Comparative Example 8] (Preparation of first mixture of one-terminal carboxylated ethyl cellulose and polyurethane resin) A binder solution was prepared under the same conditions as in Comparative Example 1, except that the different resin was changed to a polyurethane resin having an amino group (a prepolymer consisting of polyester polyol PMPA (poly(3-methyl-1,5-pentanediol adipate)diol), polyether polyol PPG (poly(propylene glycol)diol), and diisocyanate IPDI (isophorone diisocyanate), to which IPDI (isophorone diamine) and DETA (diethylenetriamine) were added as chain extenders and ethylenediamine as a terminator, and the number average molecular weight Mn was 26,000).

[0090] [Comparative Example 9] (Preparation of the first mixture of one-terminal carboxylated ethyl cellulose and polyether resin) A binder solution was prepared under the same conditions as in Comparative Example 1, except that the different resin was changed to a polyether resin having a hydroxyl group (mPEG, number average molecular weight Mn=10000).

[0091] [Comparative Example 10] (Preparation of the fourth mixture of one-terminated ethyl cellulose and aliphatic polyester resin) A binder solution was prepared under the same conditions as in Comparative Example 2, except that the different resin was changed to an aliphatic polyester resin having a hydroxyl group (polycaprolactone, number average molecular weight Mn=45000).

[0092] The following Synthesis Examples 1 to 3 are copolymers in which a cellulose derivative having a carboxyl group at one end is linked to a different type of resin via a binder.

[0093] <Synthesis Example 1> (Synthesis of cellulose derivatives in which allyl alcohol has been introduced into the first one-terminal carboxylated ethyl cellulose) 10 parts by mass of the first one-terminal carboxylated ethyl cellulose was dried under reduced pressure, and 90 parts by mass of ethyl acetate was added and dissolved under a nitrogen atmosphere at 50° C. To the obtained solution, 0.045 parts by mass of allyl alcohol, diisopropylcarbodiimide as a condensing agent in an amount 1.1 times the molar amount of the cellulose derivative having a one-terminal carboxyl group, and dimethylaminopyridine as a reaction accelerator in an amount 0.01 times the molar amount of the condensing agent were added, and the mixture was reacted by stirring at a temperature of 50° C. for 24 hours to prepare a binder solution.

[0094] Thereafter, the ethyl acetate was distilled off to obtain a solid, and the cellulose derivative according to Synthesis Example 1 in which allyl alcohol was introduced into the cellulose derivative having a terminal carboxyl group was prepared.

[0095] The cellulose derivative obtained according to Synthesis Example 1 was analyzed by FT-IR, 1 H-NMR analysis confirmed the formation of an ester bond and an allyl group derived from allyl alcohol, confirming the progress of the reaction.

[0096] <Synthesis Example 2> (Synthesis of polyvinyl acetal resin derivatives in which methacrylic acid has been introduced into polyvinyl acetal resins having hydroxyl groups) As another type of resin, 10 parts by mass of a polyvinyl acetal resin having hydroxyl groups ("BL-S" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn = 27000) was dried under reduced pressure, and 90 parts by mass of ethyl acetate was added and dissolved in a nitrogen atmosphere at 50 ° C. To the resulting solution, 0.032 parts by mass of methacrylic acid, diisopropylcarbodiimide as a condensing agent in an amount of 1.1 times the number of moles of the polyvinyl acetal resin having hydroxyl groups, and dimethylaminopyridine as a reaction accelerator in an amount of 0.01 times the number of moles of the condensing agent were added, and the mixture was stirred at a temperature of 50 ° C. for 24 hours to react, producing a binder solution.

[0097] Thereafter, the ethyl acetate was distilled off to obtain a polyvinyl acetal resin derivative according to Synthesis Example 2 in which methacrylic acid was introduced into the polyvinyl acetal resin having a hydroxyl group, as a solid.

[0098] The polyvinyl acetal resin derivative obtained in Synthesis Example 2 was analyzed by FT-IR, 1 H-NMR analysis confirmed the formation of ester bonds and vinyl groups derived from methacrylic acid, confirming the progress of the reaction.

[0099] <Synthesis Example 3> (Synthesis of polyvinyl acetal resin derivatives in which thioglycolic acid has been introduced into polyvinyl acetal resins having hydroxyl groups) 10 parts by mass of a polyvinyl acetal resin having hydroxyl groups ("BL-S" manufactured by Sekisui Chemical Co., Ltd., number average molecular weight Mn = 27000) was dried under reduced pressure, and 90 parts by mass of ethyl acetate was added and dissolved in a nitrogen atmosphere at 50°C. 0.034 parts by mass of thioglycolic acid, diisopropylcarbodiimide as a condensing agent in an amount of 1.1 times the number of moles of the polyvinyl acetal resin having hydroxyl groups, and dimethylaminopyridine as a reaction accelerator in an amount of 0.01 times the number of moles of the condensing agent were added to the resulting solution, and the mixture was stirred at a temperature of 50°C for 24 hours to react, producing a binder solution.

[0100] Thereafter, the ethyl acetate was distilled off to obtain, as a solid, the polyvinyl acetal resin derivative according to Synthesis Example 3 in which thioglycolic acid was introduced into the polyvinyl acetal resin having a hydroxyl group.

[0101] The polyvinyl acetal resin derivative obtained in Synthesis Example 3 was analyzed by FT-IR, 1 H-NMR analysis confirmed the presence of an ester bond, confirming the progress of the reaction.

[0102] Next, the resin derivatives according to Synthesis Examples 1 to 3 were combined to synthesize copolymers according to Examples 15 and 16, respectively.

[0103] [Example 15] (Synthesis of copolymers of cellulose derivatives having allyl alcohol introduced therein and polyvinyl acetal resin derivatives having methacrylic acid introduced therein) 5 parts by mass of the cellulose derivative having allyl alcohol introduced according to Synthesis Example 1 and 5 parts by mass of the polyvinyl acetal resin derivative having methacrylic acid introduced according to Synthesis Example 2 as another resin were dried under reduced pressure, and 90 parts by mass of dihydroterpinyl acetate was added thereto and dissolved under a nitrogen atmosphere at 50° C. Next, 0.05 parts by mass of azobisisobutyronitrile was added as a polymerization initiator to this solution, and the reaction was carried out at 80° C. for 5 hours to prepare a binder solution containing a copolymer of the cellulose derivative having allyl alcohol introduced according to Synthesis Example 1 and the polyvinyl acetal resin derivative according to Synthesis Example 2.

[0104] For the analysis of the obtained copolymer, the binder solution was poured into methanol to precipitate the binder, which was then dried under reduced pressure to obtain a solid copolymer.

[0105] The copolymer obtained was analyzed by FT-IR, 1 Analysis by H-NMR confirmed the disappearance of allyl and vinyl groups, and analysis by GPC showed that the number average molecular weight was larger than that of the raw material resin, confirming the progress of the reaction.

[0106] [Example 16] (Synthesis of copolymers of cellulose derivatives having allyl alcohol introduced therein and polyvinyl acetal resin derivatives having thioglycolic acid introduced therein) Except for changing the different resin to the polyvinyl acetal resin derivative having thioglycolic acid introduced therein according to Synthesis Example 3, the reaction was carried out under the same conditions as in Example 15 to prepare a binder solution containing a copolymer. From this binder solution, a copolymer of the cellulose derivative having allyl alcohol introduced therein according to Synthesis Example 1 and the polyvinyl acetal resin derivative according to Synthesis Example 3 was obtained.

[0107] The copolymer obtained was analyzed by FT-IR, 1 Analysis by H-NMR confirmed the disappearance of allyl groups, and analysis by GPC confirmed the progress of the reaction, as the number average molecular weight was larger than that of the raw material resin.

[0108] [Example 17] (Preparation of binder resin in which a terminal functional group derived from a different type of low molecule has been introduced into a cellulose derivative having a terminal carboxyl group) 10 parts by mass of the fourth one-terminal carboxylated ethyl cellulose as a cellulose derivative having a one-terminal carboxyl group was dried under reduced pressure, and 90 parts by mass of ethyl acetate was added and dissolved under a nitrogen atmosphere at 50° C. To the obtained solution, ethanol was added in an amount 5 times the number of moles of the fourth one-terminal carboxylated ethyl cellulose, diisopropylcarbodiimide was added in an amount 5 times the number of moles of the condensing agent, and dimethylaminopyridine was added in an amount 0.01 times the number of moles of the condensing agent as a reaction accelerator, and the mixture was stirred at a temperature of 50° C. for 24 hours to carry out a reaction, thereby preparing a binder solution.

[0109] Thereafter, the ethyl acetate and ethanol were distilled off to obtain a solid binder resin in which a terminal functional group was introduced into a cellulose derivative having a carboxyl group at one end.

[0110] The obtained binder resin was analyzed by FT-IR, 1Analysis by H-NMR confirmed the formation of ester bonds, and analysis by GPC confirmed that the number average molecular weight was larger than that of the raw material resin, confirming the progress of the reaction.

[0111] Thereafter, in order to prepare a conductive paste, 10 parts by mass of the obtained binder resin was dissolved in 90 parts by mass of dihydroterpinyl acetate to prepare a binder solution.

[0112] [Preparation of conductive paste] BET diameter 177nm (SSA (specific surface area) = 3.8m 2 44.0 parts by mass of nickel powder with a BET diameter of 13 nm (SSA = 77 m 2 A conductive paste was prepared by mixing 2.9 parts by mass of ceramic powder mainly composed of barium titanate (0.7 parts by mass of a polycarboxylic acid-based polymer dispersant, 21.2 parts by mass of the binder solutions obtained in the above Examples and Comparative Examples, and 31.2 parts by mass of dihydroterpineol acetate, and dispersing the mixture in a three-roll mill.

[0113] The dispersion method is not limited to the above, and various methods such as a roll mill, a ball mill, a bead mill, and high pressure dispersion can be used.

[0114] [Evaluation of resin components in paste] The conductive paste containing the binder solution according to Example 1 and prepared as described above was centrifuged (Hitachi Koki "CS100FNX", rotation speed 29000 rpm, 20 minutes) to precipitate the nickel particles and ceramic particles, and the supernatant was separated. After separating the polymer components using GPC (gel permeation chromatography), the polymer components were treated with HPLC (high performance liquid chromatography), and it was confirmed that there was a peak between the peak corresponding to ethyl cellulose and the peak corresponding to PVB (polyvinyl butyral). This showed that the synthesis of the copolymer was successful.

[0115] In addition, the polymer components separated by GPC were dried, and the supernatant was treated with trimethylsilyl (TMS) and analyzed by NMR. 1 No H-NMR peaks were observed.

[0116] In addition, the above-mentioned dried supernatant solid was reacted with sodium hydroxide in a water-methanol mixed solvent and subjected to thermal hydrolysis. After separating the polymer components by GPC, the cellulose-based resin was separated from the polymer components by HPLC, and the dried solid was converted into TMS and measured by NMR. 1 H-NMR peaks were confirmed.

[0117] From these, it was confirmed that the binder according to Example 1, which was synthesized from the first one-terminal carboxylated ethyl cellulose and the polyvinyl acetal resin, was present in the paste. It was also confirmed that the binder according to Example 1, which was synthesized from the first one-terminal carboxylated ethyl cellulose and the polyvinyl acetal resin, was not altered in the paste.

[0118] [Evaluation of smoothness of electrode coating film] The smoothness of the electrode coating film of the prepared conductive paste was evaluated by the following procedure.

[0119] The conductive paste sample was applied to a glass substrate using a 9 μm doctor blade, and the smoothness of the electrode coating film after heating and drying was evaluated using a hybrid laser microscope (OPTELICS) manufactured by Lasertec Corporation. The measurement conditions for the hybrid laser microscope were: measurement mode: surface profile, magnification: 50x, vertical resolution: 0.04 μm, measurement area: 1.44 mm 2 It was decided.

[0120] When the compatibility between the cellulose derivative and another type of resin is low, agglomerates are formed, and when the degree of cross-linking is high, gelation occurs. However, these products are not the main components, and it is assumed that they occur only rarely. Therefore, the Sz (in-plane distribution of maximum height) value, which is the sum of Sp (in-plane distribution of maximum peak height) and Sv (in-plane distribution of maximum valley depth) in the electrode coating film, was calculated. The smoothness was evaluated according to the following evaluation criteria for the average value after measuring 16 points. ⊚: Sz value is less than 1.80 μm. ◯: The Sz value is 1.80 or more and less than 1.90 μm. ×: Sz value is 1.90 μm or more.

[0121] The number average molecular weights Mn and the results of the smoothness evaluation of the copolymers according to the examples and comparative examples are summarized in Table 3.

[0122] [Table 3]

[0123] From the results of Examples 1 to 16 in Table 3, it was confirmed that the conductive paste contains a binder in which a carboxyl group at one end of the molecular chain of a cellulose resin is bonded to another type of resin, thereby improving the compatibility between the cellulose resin and the other type of resin and not impairing the smoothness of the coating film. This effect can be obtained, for example, by using alkyl cellulose as the cellulose resin and any of polyvinyl acetal resins, acrylic resins, polycarbonate resins, polyurethane resins, polyether resins, and polyester resins having hydroxyl groups or amino groups as the other type of resin, and the content ratio of the cellulose resin to the other type of resin is reliably obtained within the range of 80:20 to 20:80 in mass conversion.

[0124] From Example 17 in Table 3, it was confirmed that the smoothness of the coating film was not impaired by the conductive paste containing a cellulose-based resin having an ester group as a functional group at one end of the molecular chain.

[0125] Although the above describes an embodiment of a conductive paste containing nickel particles as metal particles, it is understood that as long as the binder can form a smooth coating film in combination with nickel particles, the same effect can be obtained even if it is combined with other metal particles such as copper particles, or with ceramic particles such as BaTiO3 particles. From this, it is understood that the inorganic particles contained in the paste for electronic components can be any inorganic particles.

Claims

1. The composition includes inorganic particles, a dispersant, a binder, and an organic solvent, The binder is (A) A copolymer represented by the following general formula 1 or the following general formula 2 in which a first bond at one end of a molecular chain of a cellulose-based resin is linked to another type of resin or another type of low molecular weight molecule via an ester bond or an amide bond; or (B) the first bond at one end of the molecular chain of the cellulose-based resin is an ester bond or an amide bond, and the binder (R 3 A copolymer represented by the following general formula 3 or 4, in which the second bond (X) is linked to another resin via (X) A paste for electronic components comprising at least 【Chemistry 1】 【Chemistry 2】 In the formula, R 1 represents a hydrogen atom, an alkyl group, a hydroxyalkyl group, or an acyl group; R 2 indicates another type of resin or an alkyl group. 【Chemistry 3】 【Chemistry 4】 In the formula, R 1 represents a hydrogen atom, an alkyl group, a hydroxyalkyl group, or an acyl group; R 4 indicates a different type of resin, R 3 represents an alkyl or sulfide containing linking agent, and X represents an ester or amide bond.

2. 2. The paste for electronic components according to claim 1, wherein the cellulose-based resin is a cellulose ether having a carboxyl group at one end of the molecular chain.

3. 3. The paste for electronic components according to claim 2, wherein the cellulose ether is an alkyl cellulose.

4. 4. The paste for electronic components according to claim 1, wherein the different resin includes at least one selected from the group consisting of a polyvinyl acetal resin having a hydroxyl group or an amino group, an acrylic resin, a polycarbonate resin, a polyurethane resin, a polyether resin, and a polyester resin.

5. 2. The paste for electronic components according to claim 1, wherein a content ratio of said cellulose-based resin to said other resin is in a range of 80:20 to 20:80 in terms of mass.

6. 4. The paste for electronic components according to claim 1, wherein the inorganic particles include at least one of ceramic particles and metal particles.

7. 7. The paste for electronic components according to claim 6, wherein the ceramic particles contain at least one element selected from the group consisting of Ba, Ti, Ca, Zr and Sr.

8. The paste for electronic components according to claim 6 , wherein the metal particles contain at least one metal selected from the group consisting of Cu, Ni, Au and Ag.

9. 4. The paste for electronic parts according to claim 1, wherein the dispersant is a polymer dispersant.

10. The paste for electronic components according to claim 9, wherein the polymer dispersant is a polycarboxylic acid-based dispersant.

11. The R 2 The paste for electronic parts according to any one of claims 1 to 3, wherein the alkyl group has 1 to 4 carbon atoms.

Citation Information

Patent Citations

  • Printer

    JP1977024722A

  • Method of electrolytically oxidizing metallic ions

    JP1977099904A

  • Electrode forming composition, electrode manufactured by using the same, and solar cell

    JP2016213440A

  • Polymer compound and polymer composition containing the same, and inorganic particle-containing composition

    JP2020029479A

  • Method for producing binder resin, method for producing resin composition, binder resin, and resin composition

    WO2015107811A1